Biological And Physiochemical Studies Of Oleyl Palmitate As An Active Agent In Cosmetic Formulation - Nurul Fadhilah Abdul Halim; Salina Mat Radzi; Maryam Mohd Rehan; Nor Amalina Mohd Amin; Nurul Jannah Abdul Rahman (IIUM Press, 2026)
Indexed by MyCite